Performance study of SC wall based on experiment and parametric analysis - Ge, Qi; He, Tao; Xiong, Feng; Zhao, Peng; Lu, Yang; Liu, Yang; Zhou, Ning (Journal of Civil Engineering and Management, 2020)
Reverse cyclic lateral testing was undertaken to investigate the seismic behavior of 1/4 scale steel-plate concrete (SC) composite walls. The experimental program involved seven SC wall pier specimens. A new chamber structure is proposed, using steel diaphragms to connect the two steel faceplates to each other and to divide the SC wall pier into two parts. Conventional wall specimens failed mainly by tensile fracture of the concrete at the junction of the wall side and wall base, crushing of the concrete at the toe of the wall, or buckling of the steel faceplate. Tearing of the welded joints at the steel faceplates and steel diaphragm, buckling of steel, steel diaphragms being pulled out, tensile fracture and crushing of the concrete were the main failure modes of the chamber structure walls. A parametric numerical analysis in ABAQUS was developed to investigate the effects of the stiffening rib, steel web amount, material strength, shear-span ratio, and axial compression ratio on the seismic response of SC walls. The chamber structure of the SC wall piers can improve the peak load, ductility, and energy-dissipating capacity. The steel faceplate thickness and stiffening ribs can improve the behavior of SC wall piers.